Location Choices of highly Educated Foreign Workers: the Importance of Urban Amenities - Or Levkovich; Jan Rouwendal (Tinbergen Institute, 2014)
In the globalized economy the presence of migrants is essential for urban and regional growth, and it is therefore important to know what makes a city an attractive place for highly skilled migrants. This paper aims to shed light on this issue by considering the location choice of highly-educated foreign workers, and if and how their valuation of urban amenities differs from domestic workers. To do so, we apply a residential location-choice model to estimate the attractiveness of residential locations in the Dutch Randstad for low and high-skilled, domestic and foreign workers, and calculate and compare their willingness to pay for each of these amenities.
Keywords: F68; R53; R11; 330; urban amenities; foreign workers